2012
DOI: 10.1080/10962247.2012.726693
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aerosol emissions from wastewater aeration basins

Abstract: The emission of particulate matter (PM 10 and PM 2.5 ) and ammonia (NH 3 ) by aeration processes at wastewater treatment plants (WWTPs) with and without odor control units was examined. Local concentrations of PM 2.5 , PM 10 , and NH 3 at the aeration basins were within urban ranges. Emission fluxes of NH 3 and PM 2.5 for a medium-sized WWTP were determined to be 136 g day À1 and 43 g day À1 , respectively, which are not substantial emission fluxes for urban environments. Odor control treatment using a granula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Although the direct inhibition of sulphur oxidising bacteria by H 2 S alone has not been noted, the reaction of SO 4 2À oxidised from H 2 S with another malodorous sewer gas, NH 3 , to form (NH 4 ) 2 SO 4 has been shown to inhibit both SOB (Nixon, 1997) and SRB (Pikaar et al, 2014). Ammonia gas was not monitored in this study, however this gas with H 2 S and volatile organic compounds make up typical constituents of sewer gases (Hernandez et al, 2012;Kim et al, 2013;Upadhyay et al, 2013) and may have also impacted the growth of both SRB and SOB. Our results show the potential roles played by the organic acid and H 2 S metabolites in the growth and metabolism of fungi and acidophilic bacteria.…”
Section: Effect Of H 2 S Concentrationmentioning
confidence: 87%
“…Although the direct inhibition of sulphur oxidising bacteria by H 2 S alone has not been noted, the reaction of SO 4 2À oxidised from H 2 S with another malodorous sewer gas, NH 3 , to form (NH 4 ) 2 SO 4 has been shown to inhibit both SOB (Nixon, 1997) and SRB (Pikaar et al, 2014). Ammonia gas was not monitored in this study, however this gas with H 2 S and volatile organic compounds make up typical constituents of sewer gases (Hernandez et al, 2012;Kim et al, 2013;Upadhyay et al, 2013) and may have also impacted the growth of both SRB and SOB. Our results show the potential roles played by the organic acid and H 2 S metabolites in the growth and metabolism of fungi and acidophilic bacteria.…”
Section: Effect Of H 2 S Concentrationmentioning
confidence: 87%
“…The faulty sewage-drainage system was linked to the SARS-CoV-1 outbreak among the residents living in the surrounding buildings [95] wherein aerosolized particles play a major role in virus spreading [96] . The transportation of CoV in water potentially increases the virus spread through the aerosol formation [97] particularly during wastewater discharge and flow in the drainage system, pumping stations and WWTPs.…”
Section: Environmental Exposure Routes – Virus Transmissionmentioning
confidence: 99%
“…Unit operation in WWTP such as biological oxidation normally employed for treatment of sewage/wastewater influences the aerosol formation due to aeration operation. Particulate matter emissions from aeration basins demonstrated that wastewater material is getting aerosolized and transported beyond the facilities [97] . The potential for viruses to be aerosolized was studied and monitored by spiking Ebola virus surrogates (MS2 and Phi6) in wastewater systems (toilets, lab-scale aeration basin, and lab-scale model of converging sewer pipes) [110] .…”
Section: Environmental Exposure Routes – Virus Transmissionmentioning
confidence: 99%
“…The SSI using the dry electrostatic precipitator method recorded the highest contribution emission of PM 2.5. Next, 24 stationary air samples were taken from a WWTP study in the United States (37). In this strong-quality study, it was found that the emission of PM 2.5, PM 10, and NH 3 at both types of aeration basin (open and closed system) were within turban range.…”
Section: Pm 25 Concentration In the Airmentioning
confidence: 99%